SIMULASI JARINGAN JALAN DI KOTA SEMARANG BERBASIS ALGORITMA FLOYD-WARSHALL UNTUK MENANGANI MASALAH LINTASAN TERPENDEK - Harsono, Harsono; Mulyono, Mulyono; Suyitno, Amin (Unnes Journal of Mathematics, 2016)
This study aimes to know the result of simulation program of road network by using Floyd-Warshall algorithm and visual basic programing. This study also aims to prove that the manual calculation is not different with the simulation of road networking in finding the shortest path of a graph. The method include (1) problem identification, (2) study of litetature, (3) data collection, (4) desainning and constructing simulation program, (5) implementasion of simulation, (6) evaluation of simulation program, (7) drawing conclution. Based on road network data of semarang city with is represented in a form of graph and running simulation Floyd-Warshall algorithm which is the result of desainning and creating the program by using visual basic programming. This simulation resulting shortest path for finding from start verteks to destination verteks after represented to simulation program.Based result manual calculation and the simulation Floyd-Warshall algorithm of this graph is not different